The Effect of Water Temperature during Cold-Water Immersion on Recovery from Exercise-Induced Muscle Damage - Vieira, A.; Siqueira, A. F.; Ferreira-Junior, J. B.; do Carmo, J.; Durigan, J. L. Q.; Blazevich, A.; Bottaro, M. (International Journal of Sports Medicine, 2016)
This study investigated the effects of 5 and 15°C cold-water immersion on recovery from exercise resulting in exercise-induced muscle damage. 42 college-aged men performed 5×20 drop-jumps and were randomly allocated into one of 3 groups: (1) 5°C; (2) 15°C; or (3) control. After exercise, individuals from the cold-water immersion groups had their lower limbs immerged in iced water for 20 min. Isometric knee extensor torque, countermovement jump, muscle soreness, and creatine kinase were measured before, immediately after, 24, 48, 72, 96 and 168 h post-exercise. There was no between-group difference in isometric strength recovery (p=0.73). However, countermovement jump recovered quicker in cold-water immersion groups compared to control group (p<0.05). Countermovement jump returned to baseline after 72 h in 15°C, 5°C group recovered after 96 h and control did not recovered at any time point measured. Also, creatine kinase returned to baseline at 72 h and remained stable for all remaining measurements for 15°C group, whereas remained elevated past 168 h in both 5°C and control groups. There was a trend toward lower muscle soreness (p=0.06) in 15°C group compared to control at 24 h post-exercise. The result suggests that cold-water immersion promote recovery of stretch-shortening cycle performance, but not influence the recovery of maximal contractile force. Immersion at warmer temperature may be more effective than colder temperatures promoting recovery from strenuous exercise.
Keywords: Cryotherapy; muscle function; functional performance